HTML Tag Structure Based Content Retrieval from Web Pages - v, S.S (International Journal of Computer Sciences and Engineering, 2022)
With the immense quantity of information in the World Wide Web, the World Wide Web (WWW) contains enormous amounts of web pages which are accessible by users. Web pages formatted in HTML (i.e. Hyper Text Markup Language) are found on this network of computers. All the Web pages, pictures, videos and other online content can be accessed via a Web browser. This provides a very useful and helpful means of collecting information. Information retrieval systems can help to retrieving the relevant information from web documents. This process of information retrieval involves three stages such as identifying the documents want to be processed, writing of query and use of searching mechanism to retrieve the relevant web document information. This paper discuss how HTML Tags structure of web page are useful for retrieval of main or informative content from web pages for efficient web mining operations.